Retinal Neurodegeneration on the Early Type 2 Diabetes Mellitus - Teguh Susilo; Freddy Rares; Herny Poluan (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: retinal neurodegeneration has been known to happen before any vascular lesion detected in the histological study in diabetic induced rats. This research was aimed to analyse neurodegeneration of the retina anatomically in vivo on the diabetic patient before any lesion could be seen clinically as the manifestation of microvascular disease.Method: comparative observational research was conducted on two groups, i.e. normal and NDR (no diabetic retinopathy) which fulfil the inclusion and exclusion criteria. The macular thickness of each group measured with Stratus OCT machine. The collected data was analysed statistically.Result: samples of 42 eyes collected from 21 patients in the normal group and 41 eyes collected from 22 patients in the NDR group. The normal group consisted of 20 (48%) males and 22 (55%) females while NDR group consisted of 17 (41%) males and 24 (59%) females. The age mean was 51.33 years on the normal group and 53.44 years on the NDR group. The sex and the age difference between the two groups had no statistical significance. Statistical analysis on the two groups showed very significant reduction of the macular thickness apply to all macula region except for the foveal minimal and superior outer which only showed significant reduction. The thinning of macula showed a greater extends of reduction on the fovea and inner ring compare to outer ring.Conclusion: there was thinning of macula as result of retinal neurodegeneration on the early diabetic patient before any microvascular lesion could be seen (no diabetic retinopathy/NDR).Â Keywords: neurodegeneration, diabetes mellitus, macular thickness, OCT